The Strategic Partnership between Russia and the United States: Historical Experience and Prospects - Askar A. Akayev; Yuri V. Yakovets (Евразийская интеграция: экономика, право, политика)
General features characterize all six components of the genotype of the Eurasian and North American civilization — naturalecological, sociodemographic, technological, economic, socio-cultural, public-political and geopolitical. Overcoming the current confrontation and move towards the strategic partnership of Russia and the United States is dictated by the objective laws of the development of society and its interaction with nature in a new historical stage dynamics of civilizations. Civilizational approach provides an opportunity to define a system of long-term priorities the strategic partnership of Russia and the United States based on genotype structure of civilization and indigenous interests of the peoples of the two countries.